Phase‐Controlled Synthesis of Monolayer W1−xRexS2 Alloy with Improved Photoresponse Performance. Issue 20 (22nd April 2020) - Wang, Zixuan; Zhao, Xiaoxu; Yang, Yuekun; Qiao, Lei; Lv, Lu; Chen, Zhang; Di, Zengfeng; Ren, Wei; Pennycook, Stephen J.; Zhou, Jiadong; Gao, Yanfeng
Abstract: Tuning bandgap and phases in the ternary 2D transition metal dichalcogenides (TMDs) alloys has opened up unexpected opportunities to engineer optoelectronic properties and explore potential applications. In this work, a salt‐assisted chemical deposition vapor (CVD) growth strategy is reported for the creation of high‐quality monolayer W1− x Re x S2 alloys to fulfill a readily phase control from 1H to DT by changing the ratio of Re and W precursors. The structures and chemical compositions of doping alloys are confirmed by combining atomic resolution scanning transmission electron microscopy‐annular dark field imaging with energy dispersive X‐ray spectroscopy (EDS) and X‐ray photoelectron spectroscopy, matching well with the calculated results. The field‐effect transistors (FETs) devices fabricated based on 1H‐W0.9 Re0.1 S2 monolayer exhibit a n‐type semiconducting behavior with the mobility of 0.4 cm 2 V −1 s −1 . More importantly, the FETs show high‐performance responsivity with a value of 17 µA W −1 in air, which is superior to that of monolayer CVD‐grown WS2 . This work paves the way toward synthesizing monolayer ternary alloys with controlled phases for potential optoelectronic applications. Abstract : Here, a salt‐assisted CVD strategy on the synthesis of monolayer W1− x Re x S2 alloys is reported. The 1H and DT structures are examined by STEM‐ADF. The 1H‐W0.9 Re0.1 S2 photodetector displays a high responsivity of 17 µA W −1 in air, demonstrating that alloying is a good way for improving the optoelectronic performance of 2D TMDs.